Peran Dinas Pariwisata dan Kebudayaan dalam Pengelolaan Objek Wisata Aroma Pecco Kabupaten Kerinci Provinsi Jambi - Rozia, Hapiza; Dewi, Ratna; Mardiah, Ainun (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study looks at how the Tourism and Cultural Office manages the Aroma Pecco Tourist Site in Kerinci District, Jambi Province. The research aims to find out if the office is doing its job well and what challenges it faces. The findings show that the office has done some things well, but there are obstacles that prevent it from fully achieving its goals. One big problem is the issue of land ownership, as the site is currently controlled by PTPN VI Kebun Teh Kayu Aro. The study suggests making detailed plans and resolving the land ownership problem to improve the situation. Overall, the study helps us understand the challenges faced by the office in managing the Aroma Pecco Tourist Site and gives ideas for better tourism management in the future.